Injury Prevention and Rehabilitation in Professional Football: A Sports Science Perspective - Ahmad Faisal, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of the research study is to determine injury prevention and rehabilitation in professional football. This research study is based on the sports science perspectives. The interplay between physical skill and player well-being in the dynamic world of professional football is methodically choreographed through the prism of sports science. This research investigates into the broad uses of sports science in injury prevention and recovery, delving into the detailed techniques used to protect athletes from possible setbacks while optimizing their performance. for measuring, the research study used smart PLS software and generated informative results, including descriptive statistics, the correlation coefficient analysis, and a smart PLS Algorithm model. Proactive methods in injury prevention, such as personalized fitness tests, tailored strength programmers, and the incorporation of cutting-edge technology like wearables and virtual reality, create the groundwork for a robust playing field. Injuries will inevitably become a part of the study, requiring a smooth transition into the world of recovery. Individualized rehabilitation programmers are used in this phase, where technology-driven biomechanical analysis and psychological assistance work together to ensure physical healing and the restoration of athletes' mental and emotional well-being. The overall research found a direct and significant relation to injury prevention and rehabilitation in professional footballs. As we negotiate this mix of competence and care, the future offers further advances, stretching the frontiers of sports science in professional football and assuring athletes' long-term brilliance on the big stage.